ANALISIS STRATEGI PENGEMBANGAN INDUSTRI JAMU TRADISIONAL DI KABUPATEN BANGKALAN - MADURA - Risa Dewi Munica; Millatul Ulya; Muhammad Fakhry (AGROINTEK, 2017)
Data of Disperindag Bangkalan Regency (2015), shows that Bangkalan Regency has 20 herbal medicine industries. After doing research survey there are some herbal medicine industries that have been inactive, so that this research is conducted to find out alternative strategy that can be used as an effort to develop herbal medicine industry in Bangkalan Regency. This research used analysis of internal environment (IFE) and external (EFE), External-internal matrix (IE), SWOT and QSPM matrix (Quantitative Strategic Planning Matrix). There are 16 internal factors and 11 external factors. As for alternative strategy there are 5 alternatives obtained from SWOT matrix and IE matrix. In the QSPM matrix, the priority of strategy is 1. Maintain and improve product quality, 2. Increase promotional activities and expand the marketing area,3. Improving relationships with government and other agencies, 4. Maintain company image, and 5. Develop cooperation with other industries outside the region